Modification in the sensory profile of coffee through anaerobic fermentation techniques in processing methods - Silvestre, João Pedro de Miranda; Voltolini, Giovani Belutti; Alecrim, Ademilson de Oliveira; Malta, Marcelo Ribeiro; Silva, Larissa Cocato da; Nadaletti, Denis Henrique Silva (Scientia Agraria Paranaensis, 2021)
One technique that has been drawing the attention of producers is the induced fermentation of the fruits. In the induced fermentation process, the fermentation speed is increased, but environmental interferences with different microbiota can alter the fermentation process, making it difficult to repeat the results. The objective was to induce anaerobic fermentations in coffee fruits, through different processes, aiming at modifying the sensory profile of the beverage. The experiment was conducted in 2019, with ‘Mundo Novo IAC-379/19’ coffee fruits, which came from full harvest, with 70% of fruits in the parchment stage. On the day of harvest, the coffee was separated into 78 experimental plots, each containing 10 L. The treatments used were: addition extract of Citrus reticulata, Carica papaya, Ananas comosus, Eucalyptus spp. leaf and addition of sugar, at concentration of 10% in aqueous solution (stored in 12 L buckets) and treatment with water only. 24 and 48h fermentation periods were tested, besides two processing methods, natural and with peeled fruits. In addition, the fruits were tested without induced fermentation for natural and peeled coffee. It is concluded that the treatment with fermentation induced for 24 h without the addition of extracts in wet processing yielded coffees of better sensory quality, with a final score of 85.33. The wet processing of coffee fruits without the addition of extracts, immersed in water for 24 h, yielded better sensory quality. The addition of Ananas comosus extracts implies a reduction in the sensory quality of coffee in the induced fermentation process.